2020
DOI: 10.1002/jclp.23009
|View full text |Cite
|
Sign up to set email alerts
|

Toward a micro‐level perspective on acculturation among U.S. Hispanic college students: A daily diary study

Abstract: Objective: The present study introduces a daily, microlevel perspective on acculturation using a sample of Hispanic college students in Miami. Methods: We conducted a 12-day diary study with a sample of first-and second-generation Hispanic college students in Miami. Outcome variables were measured on Days 1 and 12, and acculturation components (practices, identities, and values) were measured on Days 2-11. Daily fluctuations in acculturation components between Days 2 and 11 were examined as predictors of well-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 100 publications
(142 reference statements)
1
13
0
Order By: Relevance
“…Longitudinally speaking, these findings suggest that both acculturation and context of reception likely co-occur over time by mutually influencing each other, rather than occurring independently (hereafter referred as to the acculturation−perceived context of reception co-occurrences). Schwartz et al (2021) recently reported day-to-day variations in heritage and destination cultural practices, values, and identifications. Further, another recent study (Santiago et al, 2016) observed daily variations in cultural stressors among Hispanic youth.…”
Section: F I G U R Ementioning
confidence: 99%
See 2 more Smart Citations
“…Longitudinally speaking, these findings suggest that both acculturation and context of reception likely co-occur over time by mutually influencing each other, rather than occurring independently (hereafter referred as to the acculturation−perceived context of reception co-occurrences). Schwartz et al (2021) recently reported day-to-day variations in heritage and destination cultural practices, values, and identifications. Further, another recent study (Santiago et al, 2016) observed daily variations in cultural stressors among Hispanic youth.…”
Section: F I G U R Ementioning
confidence: 99%
“…The same 5-point Likert scale was used. Further details on item selection and adaptation can be found in Lee et al (2021) and Schwartz et al (2021). Daily (Days 2-11) acculturation items are presented in Table 2.…”
Section: Daily Acculturationmentioning
confidence: 99%
See 1 more Smart Citation
“…The research on college students’ national awareness and cultural acceptance falls into the psychology field ( Schwartz et al, 2021 ). National cognition and cultural acceptance is an individual’s feeling influenced by the group culture ( Anders and Olmstead, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the measurement of the AIS may have also contributed to the lack significant results. Despite the evidence that use of the AIS fluctuates daily (Schwartz et al, 2021), the way it is currently measured through the MISS reflects a more general use of the AIS, rather than its use at a single point in time, since it captures the process of how biculturals negotiate their identity over time. This goes hand in hand with how the effects of discrimination are looked at in studies analysing AIS.…”
Section: Discussionmentioning
confidence: 99%